The collapse of the Spanish Republic, 1933-1936 : origins of the Civil War - Payne, Stanley G. (New Haven : Yale University Press, 2006)
This history focuses on the crucial period that set the stage for the Spanish Civil War. The author details the political shifts that occurred including the 1933 election & the insurrection that followed. He examines the actions of key actors during these years & uses their own writings to challenge previous perceptions.
Introduction : the problem of representative government in Spain -- The republican project -- The turning point of the republic, 1933 -- The revolutionary insurrection of 1934 -- A conservative republic? 1934-1935 -- Frustration of the parliamentary system -- Toward the popular front -- The elections of February 1936 -- The left returns to power, February-March 1936 -- The left consolidates power, March-May 1936 -- Breaking down, May-June 1936 -- Competing utopias : the revolutionary movements in the spring of 1936 -- The final phase, May-July 1936 -- The military conspiracy -- The assassination of Calvo Sotelo.
Includes bibliographical references (pages 369-409) and index.
Print version record.
English.
JSTOR
Keywords: Spain -- History -- Republic, 1931-1939.; Representative government and representation -- Spain -- History -- 20th century; Espagne -- Histoire -- 1931-1939 (République); Gouvernement représentatif -- Espagne -- Histoire -- 20e siècle.; HISTORY; HISTORY -- Europe -- Western; Representative government and representation; Spain; 1900-1999; History